Benthic weathering of calcite and dunite in benthocosm experiments between Sept. 2022 and Sept. 2023 - Michael Fuhr; Andy W Dale; Klaus Wallmann; Rebecca Bährle; Habeeb Thanveer Kalapurakkal; Stefan Sommer; Timo Spiegel; Björn Buchholz; Mark Schmidt; Mirjam Perner; Sonja Geilert (PANGAEA, 2025)
Enhanced benthic weathering has been proposed to serve as a efficient negative emission strategy. The precise weathering behaviour of calcite and dunite was investigated in long-term experiments in benthocosms. These experiments were conducted between Sept. 2022 and Sept. 2023 ashore at the Kiel Fjord. The latter are large plastic containers (~0.8 m^2) that are partly filled with sediments, with constant flow-through of Baltic Sea bottom water. The sediments, obtained from Boknis Eck in the Eckernförde Bay in March 2022, were amended with calcite and dunite in triplicate (22 mol/m^2 equivalent) . Three additional benthocosms were left unamended to serve as controls. The used materials were obtained from Sibelco (dunite) and from the german Lime Stone Association (calcite). These experiments elucidate the actual weathering behavior of calcite and dunite under conditions as close to the natural system as possible. Samples were obtained using benthic chambers (chamber volume of 400 ml) that were placed on the sediment for three hours. Samples were taken at the beginning (_in) and at the end of the deployment (_out).